Interaction Design in Free/Libre/Open Source Software Development: a systematic mapping - Alves, Daniel Domingos Alves; Matos, Ecivaldo de Souza Matos (Teste, 2019)
Approaches for integrating interaction design into software development processes do not consider the specific development characteristics of free/libre/open source software (FLOSS). Researchers know the importance of integrating good practices of interaction design into the software development process. This paper aims to present a summary and analysis of methods, techniques, tools, strategies and approaches (MTTSA) to interaction design that have been proposed/used in the context of FLOSS development. A systematic mapping was performed to identify MTTSAs of interaction design proposed or used for/in the development of FLOSS. The results show that few studies have used MTTSA of interaction design in FLOSS context. No methods or techniques of interaction design proposed specifically for the development of FLOSS have found, and the majority of the selected papers do not present any type of validation through empirical studies. We hope that this paper provides an overview of studies that have used MTTSA of interaction design in FLOSS context, and becomes an initial effort to conduct new research proposals involving interaction design MTTSA and FLOSS development.